NaV6O15 microflowers as a stable cathode material for high-performance aqueous zinc-ion batteries. Issue 12 (13th February 2020) - Li, Runxia; Guan, Chao; Bian, Xiaofei; Yu, Xin; Hu, Fang
Abstract : NaV6 O15 microflowers were synthesized as a stable cathode material for aqueous zinc ion batteries, which show a high specific capacity and excellent long-term cycling performance. Abstract : Reversible aqueous zinc-ion batteries (ZIBs) have great potential for large-scale energy storage owing to their low cost and safety. However, the lack of long-lifetime positive materials severely restricts the development of ZIBs. Herein, we report NaV6 O15 microflowers as a cathode material for ZIBs with excellent electrochemical performance, including a high specific capacity of ∼300 mA h g −1 at 100 mA g −1 and 141 mA h g −1 maintained after 2000 cycles at 5 A g −1 with a capacity retention of ∼107%. The high diffusion coefficient and stable tunneled structure of NaV6 O15 facilitate Zn 2+ intercalation/extraction and long-term cycle stability.